Dispensasi Kawin, Kebijakan Pemerintah, dan Dampaknya terhadap Ketahanan Keluarga di Sulawesi Tengah - Reyva Alviona Fernanda Priskilla; Dwi Maya Loka ZM; Moh. royfandi (Ethics and Law Journal: Business and Notary, 2026)
This study aims to analyze government policies designed to curb early marriage rates and to examine the role of women in strengthening family resilience. A qualitative descriptive-analytical research method was employed, utilizing interviews, observation, and document analysis. The findings indicate that although the central government has established policies—such as revising the minimum age for marriage, tightening marriage dispensation rules, and implementing programs to delay the age of marriage—implementation in Central Sulawesi faces sociocultural and structural obstacles. Local governments have developed initiatives such as GenRe Ambassadors, village workshops, children's forums, and classes for prospective brides and grooms; however, their effectiveness remains limited due to the high volume of marriage dispensation requests, which are almost invariably granted by the courts. Women are the group most severely affected, facing limited access to education, economic opportunities, and family decision-making processes. This study underscores the importance of integrating village-based policies, women's empowerment, and the participation of traditional and religious leaders to curb the practice of early marriage. These findings are intended to serve as a reference for local governments in formulating early marriage prevention programs that are context-specific, gender-equitable, and focused on family resilience. Abstrak Penelitian ini bertujuan untuk menganalisis kebijakan pemerintah dalam menekan angka pernikahan dini serta mengkaji peran perempuan dalam penguatan ketahanan keluarga. Metode penelitian menggunakan pendekatan kualitatif deskriptif-analitis dengan teknik wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa meskipun pemerintah pusat telah menetapkan kebijakan seperti revisi batas usia perkawinan, pengetatan dispensasi kawin, dan program pendewasaan usia perkawinan, implementasi di Sulawesi Tengah menghadapi hambatan sosiokultural dan struktural. Pemerintah daerah telah mengembangkan program seperti Duta GenRe, lokakarya desa, forum anak, dan kelas calon pengantin, namun efektivitasnya masih terbatas karena tingginya permohonan dispensasi kawin yang hampir selalu dikabulkan pengadilan. Perempuan menjadi kelompok paling terdampak, dengan akses terbatas terhadap pendidikan, ekonomi, dan pengambilan keputusan keluarga. Penelitian ini menegaskan pentingnya integrasi kebijakan berbasis desa, pemberdayaan perempuan, serta partisipasi tokoh adat dan agama untuk menekan praktik pernikahan dini. Temuan ini diharapkan dapat menjadi rujukan bagi pemerintah daerah dalam merumuskan program pencegahan pernikahan dini yang lebih kontekstual, berkeadilan gender, dan berorientasi pada ketahanan keluarga. Kata kunci: kebijakan; pernikahan dini; ketahanan keluarga; pemberdayaan perempuan